Frontiers of particle physics: (World Scientific, 2003)
This volume of proceedings deals with a wide variety of topics — both in theory and in experiment — in particle physics, such as electroweak theory, tests of the Standard Model and beyond, heavy quark physics, nonperturbative QCD, neutrino physics, astroparticle physics, quantum gravity effects, and physics at the future accelerators.